National Trends in Diagnostic Imaging for Appendicitis: A Cross-Sectional Analysis Using NSQIP. Issue 6 (June 2019) - Agathis, Alexandra Z.; Miller, Michael; Divino, Celia M.
Prior studies elucidate a high predictive value of imaging to diagnose appendicitis in small, regional cohorts. This cross-sectional study uniquely analyzes diagnostic imaging in a national appendectomy population. Using the 2016 ACS NSQIP database, positive predictive values (PPVs) for CT, ultrasound (US), and MRI were evaluated using chi-squared tests. Univariate and multivariate analyses considered patient-specific factors. Imaging was performed in 94.63 per cent of 11, 841 appendectomy cases; most frequently via CT (78.69%), then combination CT and US (7.52%), US (7.15%), and MRI (0.30%). CT PPV was higher in overweight (98.70%) versus underweight patients (94.85%) ( P = 0.01). Gender and age did not impact CT PPV. Imaging from a referral site did not change CTor US PPV. Our study describes imaging frequencies and confirms high PPV. We found imaging equally predictive in women of childbearing age and elderly individuals compared with the general population. Furthermore, repeat scanning is unnecessary with prior positive imaging at outside sites.